Study on chemical composition and biological activities of essential oil of Limnophila aromatica (Lamk.) Merr. - Nguyen Thi Bich Thuyen; Tran Thanh Men; Ho Quoc Phong; Huynh Lien Huong (Vietnam Journal of Science, Technology and Engineering)
Limnophila aromatica (Lamk.) Merr. is a widely used spice and medicinal herb in many countries and Vietnam is one of them. However, there are relatively few studies on this plant, especially within Vietnam. This research focuses on the chemical composition analysed via Gas Chromatography-Mass Spectrometry (GC-MS), antioxidant activity (measured by the DPPH method), and antimicrobial properties (determined using the paper plate method) of the essential oil derived from Limnophila aromatica (Lamk.) Merr. The results show that the primary component of the essential oil is limonene (46.86%), followed by β-cis-ocimene (24.1%), α-pinene (5.69%), and 1,2-epoxy-5,9- cyclododecadiene (4.57%). The antioxidant activity was quantified with an IC50 value of 266.6±0.56 μg/ml. The antimicrobial assays demonstrated that the essential oil was effective against six of the eight tested microorganisms, including Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Bacillus subtilis ATCC 6633, Listeria innocua ATCC 33090, Bacillus cereus ATCC 14579, and Aspergillus niger ATCC 6275. These findings suggest that Limnophila aromatica has potential applications in functional foods, cosmetics, and antibiotics.